Minecraft recipes for dummies - Stay, Jesse (--For dummies., 2015)
A quick, handy reference on Minecraft recipes Want to find resources, make a shelter, craft tools, armor, and weapons, and protect yourself from monsters with Minecraft recipes? You''ve come to the right place! In a handy, portable edition that''s packed with step-by-step instructions, Minecraft Recipes For Dummies makes it easy to look up the required items and figure out which blocks you need to gather to create each item. You''ll get recipes for weapons, armor, transportation, mechanism, food, dye, wool, and brewing, as well as information on enchanting, repairing, gathering, farming, effic.